Method for inhibiting protein freezing denaturation in surimi storage process
By adding cellulose nanocrystals (CNCs) to the surizza, the problem of frozen denaturation of proteins during surizza storage is solved, and the structural stability and health characteristics of surizza are improved, providing a green and healthy cryoprotectant.
Patent Information
- Application Number
- CN202411802858.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
Fish paste is prone to protein cryodenation during storage, and existing commercial cryoprotectants have health problems and are difficult to meet the consumption needs of specific groups.
Cellulose nanocrystals (CNCs) with a wide range of natural sources are used as the cryoprotectant for surimi. By adding 1-5% CNC to the surimi and controlling the moisture content between 75-85%, it is used to inhibit the cryodenal denaturation of surimi myofibrillary protein.
CNC can effectively inhibit the damage of sushi structure and the decline in water holding capacity, improve the structural stability and oxidative stability of myofibrillar proteins, have similar or better effects as commercial antifreezes, and are friendly to healthy dietary needs.
Smart Images

Figure CN119605846A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aquatic product processing, and in particular to a method for inhibiting protein freezing denaturation during the storage of surimi. Background Art
[0002] As people gain a better understanding of nanotechnology, the research and application of new green nanomaterials in cryoprotection has become a hot topic. Nano cryoprotective materials have good surface properties and amphiphilic properties, such as graphene oxide, nanocellulose, chitosan, and nanomaterials that simulate the structure of other cryoprotective materials. Cellulose nanocrystals (CNC), as a new type of nanomaterial, not only have the basic structure and properties of cellulose such as natural non-toxicity, degradability, renewability, and high biocompatibility, but also have the characteristics of nanoparticles, such as huge specific surface area, ultra-fine structure and high transparency, high purity, high crystallinity, high strength, high Young's modulus, high reactivity, etc. It is an environmentally friendly natural material with good development and application prospects in the food field.
[0003] my country is an important bamboo shoot production area in the world, with 6.4116 million square hectares of bamboo forest, rich bamboo resources and high bamboo shoot production. However, the edible part of bamboo shoots only accounts for 27% of the whole, and a large amount of processing waste such as bamboo shoot shells and bamboo shoot heads with high fibrosis, poor taste and unsuitable for processing into food will be produced during the processing. However, due to its high dietary fiber content (about 53.7%-77.0%), it can be used as a potential source for the preparation of new, green and low-cost nanocrystalline cellulose.
[0004] Surimi is a nutritious and delicious food raw material that can provide humans with daily nutrients such as protein, unsaturated fatty acids and vitamins. Frozen preservation is usually used to reduce the water activity of surimi, reduce endogenous enzyme activity and inhibit the growth and reproduction of microorganisms, so as to maintain the nutrition and flavor of surimi. However, frozen surimi will have large temperature fluctuations, active ice crystal behavior, and large fluctuations in pH and ionic strength during production, transportation, sales and consumption, which will have a great impact on the microenvironment of the surimi system. Commercial cryoprotectants (4% sucrose + 4% sorbitol + 0.3% polyphosphate) are often added in the surimi industry to reduce the damage of ice crystal behavior to the surimi structure, inhibit lipid oxidation, and delay protein freezing denaturation. Commercial cryoprotectants provide surimi with higher calories and sweetness, which can cause health problems such as metabolic syndrome, obesity, and dental caries in the human body. They do not meet the consumption needs of specific groups of people and greatly affect market acceptance.
[0005] In view of this, the development of the frozen surimi industry should strengthen the research and development and application of new green surimi cryoprotectants from a longer-term perspective, and better enhance the ability of cryoprotectants in improving the nutritional composition of surimi, gel properties, health characteristics, and flavor of surimi products. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for inhibiting protein freezing denaturation during the storage of surimi. Among them, a new type of nanomaterial with a wide range of natural sources, abundant reserves, extremely low acquisition costs, balanced nutrition, low calories, and adaptable to the healthy dietary needs of special consumers is used as a cryoprotectant for surimi products, which inhibits the freezing denaturation of surimi myofibrillar protein during the storage of surimi, and promotes the healthy development of green agriculture and aquatic product processing industries.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for inhibiting protein freezing denaturation during the storage of surimi, comprising the following steps: Adding cellulose nanocrystals accounting for 1-5% of the mass of the surimi to the surimi to obtain a surimi sample; The surimi sample was mixed evenly in an environment of 0-10° C., and distilled water was added to control the moisture content of the surimi sample to be 75-85% by mass.
[0008] Furthermore, in the above method for inhibiting protein freezing denaturation during storage of surimi, cellulose nanocrystals accounting for 4% of the mass of the surimi are added to the surimi to obtain a surimi sample.
[0009] Furthermore, in the above method for inhibiting protein freezing denaturation during surimi storage, the surimi sample is mixed uniformly in an environment of 7-10°C.
[0010] Furthermore, in the above method for inhibiting protein freezing denaturation during storage of surimi, distilled water is added to control the water content of the surimi sample to 78% by mass.
[0011] Furthermore, the method for inhibiting protein freezing denaturation during the storage of surimi also includes the step of: the obtained surimi samples are packaged in plastic molds for shaping.
[0012] Furthermore, in the above method for inhibiting protein freezing denaturation during surimi storage, the surimi preparation method is: Cut the fish into fillets, rinse the blood off the fillets with ice water, and then use a blender to blend the fish into minced meat at high speed; The minced meat was rinsed twice with distilled water at a weight ratio of 1:4, then rinsed once with 0.25% solute mass percentage saline at the same ratio, and then centrifuged. The centrifugation parameters were: 4°C temperature, 11000 rpm speed, 15 min, to obtain fish paste.
[0013] Furthermore, in the above method for inhibiting protein freezing denaturation during surimi storage, the method for preparing cellulose nanocrystals comprises the following steps: Grinding: Grinding the bamboo shoots into powder to obtain bamboo shoot powder; Degreasing: Soak bamboo shoot powder in ethyl acetate to remove lipids, and filter with distilled water to obtain a defatted sample; Washing: extract the defatted sample, filter it after cooling, and keep the filter residue, wash the filter residue with ethanol to obtain the washed sample; Drying and crushing: Dry and crush the washed sample and pass it through a 100-mesh sieve to obtain a sieved sample; Delignification: The sieved sample was soaked in NaOH, the precipitate was collected and washed with distilled water to obtain the delignified sample; Decolorization: soak the delignified sample in H2O2 and let it stand for decolorization to obtain a decolorized sample; Hydrolysis: Add hydrochloric acid to the decolorized sample and then perform ultrasonic treatment. Collect the precipitate by centrifugation to obtain nanocellulose. Add sulfuric acid to acid-hydrolyze the nanocellulose to obtain a hydrolyzate. Washing and freeze-drying: After centrifuging the hydrolyzate, wash the precipitate with distilled water until the supernatant is turbid, homogenize, dialyze to neutrality, and freeze-dry to obtain cellulose nanocrystals.
[0014] Furthermore, in the above method for inhibiting protein freezing denaturation during surimi storage, the method for preparing cellulose nanocrystals comprises the following steps: Grinding: Grinding the bamboo shoots into powder to obtain bamboo shoot powder; Degreasing: Soak bamboo shoot powder in 4 volumes of ethyl acetate for 1 h to remove lipids, and filter with distilled water three times to obtain a defatted sample; Washing: The defatted sample was soaked in 80°C water at a mass ratio of 1:30 for 2 h, filtered after cooling, and the residue was washed three times with 78% solute mass percentage ethanol to obtain a washed sample; Drying and crushing: Place the washed sample in an oven at 55-60°C for drying, then crush it in a grinder and pass it through a 100-mesh sieve to obtain a sieved sample; Delignification: The sieved sample was immersed in 5% solute mass percentage NaOH at 50°C at a mass ratio of 1:20 and stirred for 4 h. The precipitate was collected and washed with distilled water for 3 times to obtain a delignified sample. Decolorization: The delignified sample was immersed in 8% solute mass percentage H2O2 at a mass ratio of 1:20, and allowed to stand for 24 h to obtain a decolorized sample; Hydrolysis: the decolorized sample was added to 5% hydrochloric acid at a mass ratio of 1:25, ultrasonicated at 160 W and 50 ° C for 90 min, and the precipitate was collected by centrifugation. The precipitate was added to 10% hydrochloric acid at a mass ratio of 1:25, ultrasonicated at 160 W and 40 ° C for 60 min, and the precipitate was collected and washed. The obtained precipitate was nanocellulose. The nanocellulose and 62 wt% sulfuric acid were stirred at a mass ratio of 1:20 at 37 ° C. After 1 h, 5 times the volume of distilled water was added to stop the acid hydrolysis to obtain a hydrolyzate; Washing and freeze-drying: The hydrolyzate was centrifuged at 8000 r / min for 10 min, then the precipitate was washed with distilled water until the supernatant was turbid, homogenized for 5 min, dialyzed to neutrality, and freeze-dried to obtain cellulose nanocrystals.
[0015] Furthermore, in the above method for inhibiting protein freezing denaturation during surimi storage, the bamboo shoots are bamboo shoot shells or bamboo shoot heads.
[0016] The beneficial effects of the present invention are as follows: the present invention uses natural dietary fiber CNC as an exogenous additive added to fish paste, and it is found that it has a good regulatory effect on ice crystal behavior. When used in fish paste, it can effectively inhibit the destruction of fish paste structure and the decrease in water holding capacity. At the same time, it can effectively improve the structural stability and oxidative stability of myofibrillar protein. A concentration of 4% CNC can achieve an effect similar to or better than that of commercial antifreeze. The present invention has a simple preparation process, a wide source of raw materials, and stable performance. It provides data support for the development of new green and healthy fish paste cryoprotectants, and has a broad application space in the food field. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The freezing curves of the surimi of Examples 1 to 5 and Comparative Examples 1 to 2 of the specific implementation manner of the present invention; Figure 2 The water holding capacity of the surimi of Examples 1 to 5 and Comparative Examples 1 to 2 of the specific embodiments of the present invention; Figure 3 The moisture distribution of the surimi myofibrillar protein of Examples 1 to 5 and Comparative Examples 1 to 2 according to the specific embodiments of the present invention; Figure 4 The turbidity of the surimi myofibrillar protein of Examples 1 to 5 and Comparative Examples 1 to 2 of the specific embodiments of the present invention; Figure 5 The Ca of the surimi myofibrillar protein of Examples 1 to 5 and Comparative Examples 1 to 2 of the specific embodiments of the present invention is 2+ -ATPase activity. DETAILED DESCRIPTION
[0018] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in combination with the implementation modes and the accompanying drawings.
[0019] The cellulose nanocrystals (CNC) used in the embodiments of the present application are prepared by the following method: Grinding: Grinding the bamboo shoots into powder to obtain bamboo shoot powder; Degreasing: Soak bamboo shoot powder in 4 volumes of ethyl acetate for 1 h to remove lipids, and filter with distilled water three times to obtain a defatted sample; Washing: The defatted sample was soaked in 80°C water at a mass ratio of 1:30 for 2 h, filtered after cooling, and the residue was washed three times with 78% solute mass percentage ethanol to obtain a washed sample; Drying and crushing: Place the washed sample in an oven at 55-60°C for drying, then crush it in a grinder and pass it through a 100-mesh sieve to obtain a sieved sample; Delignification: The sieved sample was immersed in 5% solute mass percentage NaOH at 50°C at a mass ratio of 1:20 and stirred for 4 h. The precipitate was collected and washed with distilled water for 3 times to obtain a delignified sample. Decolorization: The delignified sample was immersed in 8% solute mass percentage H2O2 at a mass ratio of 1:20, and allowed to stand for 24 h to obtain a decolorized sample; Hydrolysis: the decolorized sample was added to 5% hydrochloric acid at a mass ratio of 1:25, ultrasonicated at 160 W, 50 ° C for 90 min, and the precipitate was collected by centrifugation. The precipitate was added to 10% hydrochloric acid at a mass ratio of 1:25, ultrasonicated at 160 W, 40 ° C for 60 min, and the precipitate was collected and washed. The obtained precipitate is nanocellulose. The nanocellulose and 62 wt% sulfuric acid were stirred at a mass ratio of 1:20 at 37 ° C. After 1 h, 5 times the volume of distilled water was added to stop the acid hydrolysis to obtain a hydrolyzate. Washing and freeze-drying: The hydrolyzate was centrifuged at 8000 r / min for 10 min, then the precipitate was washed with distilled water until the supernatant was turbid, homogenized for 5 min, dialyzed to neutrality, and freeze-dried to obtain cellulose nanocrystals.
[0020] Example 1 A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi and add 1% CNC by weight to the surimi; Mix the surimi samples evenly in a 0-10°C environment and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0021] Example 2 A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi and add 2% CNC to the surimi; Mix the surimi samples evenly in a 0-10°C environment and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0022] Example 3 A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi and add 3% CNC to the surimi; Mix the surimi samples evenly in a 0-10°C environment and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0023] Example 4 A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi and add CNC accounting for 4% of the surimi weight; Mix the surimi samples evenly in a 0-10°C environment and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0024] Example 5 A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi and add 5% of the mass of CNC into the surimi; Mix the surimi samples evenly in a 0-10°C environment and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0025] Comparative Example 1: This control example is the fish paste without adding protective agent as the negative control group (NC) A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0026] Comparative Example 2 This control example is a fish paste with commercial cryoprotectant (4% sucrose + 4% sorbitol) added as the positive control group (PC). A method for inhibiting protein freezing denaturation during surimi storage, comprising the following steps: Cut the fish into 5 mm slices, rinse the blood off the surface of the slices with ice tap water, and then use a blender to blend at high speed for 1 min; The minced meat was rinsed twice with distilled water at a ratio of 1:4, then rinsed once with 0.25% saline at the same ratio, and the minced fish was obtained by centrifugation (4°C, 11000 rpm, 15 min) and temporarily stored at ice temperature; Take 400 g of surimi, add 4% sucrose + 4% sorbitol to the surimi; Mix the surimi samples evenly in a 0-10°C environment and control the moisture content of all surimi samples to 78% with distilled water; The processed surimi samples were packaged in plastic molds for shaping.
[0027] Comparative Analysis In Examples 1-5 and Control Examples 1-2, the prepared surimi was divided into 6 portions, 400 g was taken in each portion, 1%, 2%, 3%, 4%, and 5% CNC-containing surimi were added as the experimental group, 4% sucrose + 4% sorbitol-containing surimi were added as the positive control group (PC), and 4% sucrose + 4% sorbitol-containing surimi were added as the negative control group (NC). Surimi samples were prepared for freeze-thaw cycle test, the surimi samples were placed in a -18°C refrigerator and frozen for 12 h, and then taken out and thawed at room temperature for 1 h as one freeze-thaw cycle, and this cycle was repeated 0, 1, 2, 3, 4, and 5 times.
[0028] Three samples were randomly selected from each of Examples 1 to 5 and Comparative Examples 1 to 2. The temperature recorder sensor probe was inserted into the volume center of the surimi sample, and the temperature was recorded once at intervals of 2 seconds, starting from the time when the sample was placed in a -18°C refrigerator and ending when the sample was thawed at room temperature for 1 hour. The change of the volume center temperature of the surimi sample over time was recorded. The freezing curve of the prepared surimi was measured.
[0029] 1. Please refer to Figure 1 , Figure 1The freezing curve of the surimi of this application is compared with the freezing temperature change trend of each surimi sample. The rapid precooling stage is not much different, and the temperature shows a rapid downward trend. In the freezing temperature change of each treatment group, according to the different CNC addition concentrations, there are also large differences. The surimi of Experimental Example 5 passes through the ice crystal formation zone the fastest, and Experimental Example 4 is second. CNC has good physical dimensions and surface properties, and its nanoscale short rod shape makes it a good crystal nucleus material. After adding CNC, water molecules can combine with CNC to quickly form crystal nuclei, thereby greatly reducing the nucleation driving force required to break through the crystallization energy barrier. CNC has good water holding properties, and its rich hydrophilic groups on the surface can greatly reduce the freezable water content in the surimi system, reduce the amount of ice crystals generated, reduce the latent heat released during the freezing process, and accelerate the rate at which the surimi sample passes through the maximum ice crystal formation zone. During the freezing process, as the CNC concentration in the surimi system increases, CNC can provide more binding opportunities for water molecules, greatly reducing the nucleation driving force required for ice crystal formation, and reducing the number of freezable ice crystals in the system. By measuring the freezing curves of different groups, it can be found that commercial antifreeze has a great advantage in accelerating the freezing rate of surimi, with the advantages of fast freezing rate, small maximum ice crystal formation zone, and small system temperature fluctuation. CNC also has a good performance in accelerating the freezing of surimi. Adding CNC at a proper high concentration can better promote the formation of ice crystals, reduce the maximum ice crystal formation zone time, and has a good cryoprotection effect.
[0030] 2. Please refer to Figure 2 , 2.0 g of the surimi samples of Examples 1 to 5 were weighed after freeze-thaw cycles, respectively, and were wrapped with two layers of filter paper and placed in a 50 mL centrifuge tube for temporary storage. Each group of samples was centrifuged at 6000 rpm, 25°C, and 10 min. The surimi samples after centrifugation were weighed and recorded as W1 (g), and the water holding rate was calculated according to the following formula: (W1 / 2.0)×100%. The water holding capacity of surimi in different freeze-thaw cycles is as follows Figure 2 shown.
[0031] Depend on Figure 2 It can be seen that with the increase in the number of freeze-thaw cycles, the water holding capacity of each group of surimi samples decreased significantly (p<0.05). However, the addition of CNC has a good inhibitory effect on the decrease in the centrifugal loss rate of surimi after freeze-thaw, and the inhibitory effect is more obvious with the increase in concentration. During the freeze-thaw process, the water in the surimi will undergo active ice crystal behavior due to temperature changes, which will aggravate the physical damage caused by ice crystals to the surimi structure and destroy the stability of the surimi system. CNC has good water holding and gel properties, which can promote the migration of free water to bound water, reduce the amount of ice crystals generated in the surimi system, and reduce the activity of ice crystal behavior. Its good gel properties can enhance the stability of the surimi system network structure and enhance the surimi structure's adsorption of water.
[0032] 5 g of surimi samples from each group were placed in a cylindrical glass container and then placed in a nuclear magnetic resonance tube. The transverse relaxation time (T2) was measured using the CPMG software program. 200 points were measured using the CPMG program, and eight scans were repeated at an interval of 3500 ms. The moisture content and moisture distribution in each group of surimi samples were determined by software analysis.
[0033] 3. Please refer to Figure 3 , Figure 3 This is the distribution diagram of T2 relaxation time of surimi in each group after 5 freeze-thaw cycles. The peak area of relaxation time after 100 ms in each group of samples is relatively large, indicating that repeated freeze-thaw has a significant effect on the degree of water binding in surimi, and the binding effect of surimi protein on water is weakened. The T2 peak values of the 4% group and the 5% group are smaller, indicating that high concentrations of CNC can increase the degree of water binding in surimi, and the effect is equivalent to that of commercial antifreeze. It shows that CNC can enhance the absorption of water molecules by surimi, and the hydrophilic groups on the surface of CNC can transform water molecules from free water to bound water, reducing the migration of water in surimi. At the same time, CNC can form a good covalent bond with surimi myofibrillar protein, stabilize the protein structure, enhance the adsorption of protein on water, and reduce the loss of water in the protein network. It is generally believed that bound water can be tightly bound to macromolecular components such as protein and lipid in surimi without causing mechanical damage and structural changes to surimi during the freezing process. Increasing the bound water content in surimi can significantly improve the stability of surimi structure and improve the cryoprotection effect. This further demonstrates that CNC can significantly improve the freeze-thaw stability of surimi.
[0034] 4. Please refer to Figure 4 , extract the myofibrillar protein from surimi after different freeze-thaw cycles, dilute the myofibrillar protein extract with pre-cooled KCl solution (0.6 mol / L KCl + 20 mmol Tris-HCl buffer) to 1 mg / mL, and measure the absorbance at 660 nm using a UV-visible spectrophotometer. Turbidity is expressed as absorbance value. The turbidity of myofibrillar protein from surimi of Control Examples 1-2 and Examples 1-5 is as follows: Figure 4 shown. Figure 4 The changes in turbidity of surimi protein under different CNC addition amounts during different freeze-thaw cycles.
[0035] As the number of freeze-thaw cycles increased, the protein turbidity in each group of samples showed an upward trend, and the upward trend was more obvious in the later stage of freeze-thaw. Among all the groups, the 4% group had the smallest upward trend in protein turbidity. As the concentration of CNC in surimi increased, the upward trend of protein turbidity became gentler. This is because in the surimi system, the abundant hydroxyl groups on the surface of CNC can be combined with the hydrophilic groups on the surface of protein molecules through hydrogen bonds to form a stable protein-CNC structure, which can reduce the damage to the protein structure caused by fluctuations in ion concentration, reduce the exposure of amino acid side chains, and avoid aggregation between protein molecules to a large extent.
[0036] 5. Please refer to Figure 5 , using the ultra-trace Ca 2+ -ATPase activity assay kit to measure Ca in myofibrillar protein 2+ -ATPase activity. Each sample was measured three times and the results were averaged in μmol / mg / min.
[0037] Figure 5 The Ca content of surimi protein with different CNC additions in different freeze-thaw cycles 2+ -Changes in ATPase activity; e.g. Figure 5 As shown in Figure 2, during the freezing and thawing process, as the number of freezing and thawing times increased, myofibrillar protein Ca 2+ -ATPase activity showed a downward trend, and the decline increased with the increase of freeze-thaw cycles. After 5 freeze-thaw cycles, the fourth freeze-thaw cycle had no significant effect on myosin Ca 2+ -ATPase activity was the most affected, while adding CNC to surimi could effectively slow down the decline of Ca 2+ -ATPase activity showed a decreasing trend during freeze-thaw cycles, and the mitigation effect was better with the increase of CNC concentration in surimi.
[0038] During the freeze-thaw cycle of surimi, the drastic temperature fluctuations increase the activity of ice crystal growth and recrystallization, resulting in the generation of a large number of large ice crystals in the surimi system. The active ice crystal behavior will squeeze the protein molecules. The generation of sharp ice crystals will aggravate the destruction of protein molecule stability, affect the conformation of protein molecules, and cause the Ca2+ of the myosin head to be blocked. 2+-ATPase exposure. The changes in ion concentration caused by the freeze-thaw process will promote the aggregation and denaturation of the myosin head and promote the degradation of myosin. CNC is a good crystal nucleus material and has a good performance in promoting ice crystal formation and inhibiting ice crystal recrystallization. During the freeze-thaw cycle, CNC reduces the activity of ice crystal behavior and reduces the impact of ice crystal behavior on the ion concentration and structural stability in the surimi system. At the same time, the rich active hydrophilic groups on the surface of CNC can covalently bind to the hydrophilic amino acids in the myosin head, thereby improving the stability of the myosin structure, effectively avoiding the aggregation of myosin and the destruction of the head conformation, and inhibiting Ca 2+ -Decrease in ATPase activity.
[0039] In summary, the present invention provides a good crystal nucleus material, CNC, which can significantly inhibit the denaturation of myofibrillar protein in surimi and improve the freeze-thaw stability of surimi. Adding CNC to surimi can accelerate the freezing rate of surimi, promote surimi to pass through the maximum ice crystal generation zone faster, and reduce the generation of large-volume ice crystals; at the same time, it can also significantly improve the water holding capacity of surimi, enhance the resistance of surimi to ice crystal behavior, and improve the stability of surimi during frozen storage. CNC can effectively avoid the mechanical damage caused by ice crystal behavior to the protein structure, slow down the protein salting out caused by changes in ion concentration, expose the internal structure, slow down the weakening of protein hydration caused by water migration, thereby improving the surface stability of the protein. And the regulation ability of CNC on ice crystal behavior and the stabilizing effect on surimi structure at a mass concentration of 4% are better than commercial cryoprotectants. It shows that CNC has good ice crystal regulation ability and myofibrillar protein structure stabilization ability. It is a new type of surimi cryoprotectant with buffering properties in the microenvironment of surimi system and can improve the gel performance and structural stability of surimi. When the addition amount is 4%, it can achieve the effect of commercial cryoprotectant, and has broad application development prospects.
[0040] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention's specification and drawings, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for inhibiting protein freezing denaturation during surimi storage, characterized in that: The steps include: Adding cellulose nanocrystals accounting for 1-5% of the mass of the surimi to the surimi to obtain a surimi sample; The surimi sample was mixed evenly in an environment of 0-10° C., and distilled water was added to control the moisture content of the surimi sample to be 75-85% by mass.
2. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: The surimi sample was obtained by adding cellulose nanocrystals accounting for 4% of the surimi mass.
3. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: Mix the surimi samples at 7-10°C.
4. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: Distilled water was added to control the moisture content of the surimi sample to 78% by mass.
5. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: The method also includes the step of: packaging the obtained surimi samples into plastic molds for shaping.
6. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: The preparation method of the surimi is as follows: Cut the fish into fillets, rinse the blood off the fillets with ice water, and then use a blender to blend the fish into minced meat at high speed; The minced meat was rinsed twice with distilled water at a weight ratio of 1:4, then rinsed once with 0.25% solute mass percentage saline at the same ratio, and then centrifuged. The centrifugation parameters were: 4°C temperature, 11000 rpm speed, 15 min, to obtain fish paste.
7. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: The preparation method of the cellulose nanocrystals comprises the following steps: Grinding: Grinding the bamboo shoots into powder to obtain bamboo shoot powder; Degreasing: Soak bamboo shoot powder in ethyl acetate to remove lipids, and filter with distilled water to obtain a defatted sample; Washing: extract the defatted sample, filter it after cooling, and keep the filter residue, wash the filter residue with ethanol to obtain the washed sample; Drying and crushing: Dry and crush the washed sample and pass it through a 100-mesh sieve to obtain a sieved sample; Delignification: The sieved sample was soaked in NaOH, the precipitate was collected and washed with distilled water to obtain the delignified sample; Decolorization: soak the delignified sample in H2O2 and let it stand for decolorization to obtain a decolorized sample; Hydrolysis: Add hydrochloric acid to the decolorized sample and then perform ultrasonic treatment. Collect the precipitate by centrifugation to obtain nanocellulose. Add sulfuric acid to acid-hydrolyze the nanocellulose to obtain a hydrolyzate. Washing and freeze-drying: After centrifuging the hydrolyzate, wash the precipitate with distilled water until the supernatant is turbid, homogenize, dialyze to neutrality, and freeze-dry to obtain cellulose nanocrystals.
8. The method for inhibiting protein freezing denaturation during surimi storage according to claim 1, characterized in that: The preparation method of the cellulose nanocrystals comprises the following steps: Grinding: Grinding the bamboo shoots into powder to obtain bamboo shoot powder; Degreasing: Soak bamboo shoot powder in 4 volumes of ethyl acetate for 1 h to remove lipids, and filter with distilled water three times to obtain a defatted sample; Washing: The defatted sample was soaked in 80°C water at a mass ratio of 1:30 for 2 h, filtered after cooling, and the residue was washed three times with 78% solute mass percentage ethanol to obtain a washed sample; Drying and crushing: Place the washed sample in an oven at 55-60°C for drying, then crush it in a grinder and pass it through a 100-mesh sieve to obtain a sieved sample; Delignification: The sieved sample was immersed in 5% solute mass percentage NaOH at 50°C at a mass ratio of 1:20 and stirred for 4 h. The precipitate was collected and washed with distilled water for 3 times to obtain a delignified sample. Decolorization: The delignified sample was immersed in 8% solute mass percentage H2O2 at a mass ratio of 1:20, and allowed to stand for 24 h to obtain a decolorized sample; Hydrolysis: the decolorized sample was added to 5% hydrochloric acid at a mass ratio of 1:25, ultrasonicated at 160 W, 50 ° C for 90 min, and the precipitate was collected by centrifugation. The precipitate was added to 10% hydrochloric acid at a mass ratio of 1:25, ultrasonicated at 160 W, 40 ° C for 60 min, and the precipitate was collected and washed. The obtained precipitate is nanocellulose. The nanocellulose and 62 wt% sulfuric acid were stirred at a mass ratio of 1:20 at 37 ° C. After 1 h, 5 times the volume of distilled water was added to stop the acid hydrolysis to obtain a hydrolyzate. Washing and freeze-drying: The hydrolyzate was centrifuged at 8000 r / min for 10 min, then the precipitate was washed with distilled water until the supernatant was turbid, homogenized for 5 min, dialyzed to neutrality, and freeze-dried to obtain cellulose nanocrystals.
9. The method for inhibiting protein freezing denaturation during surimi storage according to claim 8, characterized in that: The bamboo shoots are bamboo shoot shells or bamboo shoot heads.